k-Numerični zaklad matrike - Dobovišek, Mirko (Obzornik za matematiko in fiziko, 2013)
For any ?$n × n$? complex matrix ?$A$? and any ?$k \in \mathbb{N}, \; 1 \le k \le n$?, let ?$Λ_k(A) = \{ λ \in \mathbb{C} \colon PAP = λ P, \; P^2 = P, \; P^* = P, \; \text{rank } P = k \}$?. An overview of some new results about rank ?$k$?-numerical range is given in the article. Its convexity is proved, and a short program in MATLAB is given for computation of ?$Λ_k(A)$?.
Keywords: matrix theory; teorija matrik; numerical range; numerični zaklad; Riccati equation; Riccatijeva enačba; Matlab